Laparoscopic versus open colectomy for acute complicated diverticulitis: a comparative study of outcomes - a systematic review - Pinto, Leslie D. R.; Tapia, Gabriel A. P.; Fierro, Laura D. S.; Urdiales, Thaís R. C.; Peña, Jose A. N.; Manciati, Carla V. A.; Moscoso, Nathaly P. C.; Pujos, Bolívar L. S. (International Journal of Research in Medical Sciences, 2024)
Acute complicated diverticulitis presents a more severe form of diverticular illness frequently needing urgent medical intervention and possibly surgical therapy. The aim of this review is to gather conclusive evidence from the literature comparing laparoscopic techniques to open and conservative ones in order to determine the most effective treatment plan for complicated diverticulitis. Online databases like PubMed, Google Scholar, Cochrane, Elsevier and many others were systematically searched according to an inclusion criterion to obtain a total of 13 studies to be included in the review. 8/13 studies presented short term outcomes while 5/13 studies concluded with long term outcomes following index surgeries. Based on the end results, it can be concluded that laparoscopic surgery, in particular laparoscopic colon resection is superior to other techniques in treating complicated diverticulitis in terms of fewer short-term complications, low mortality rate better quality of life with few recurrence rates. However, other approaches have their own advantages and can be given priority based on the unique presentation of each case. The clinicians are advised to make informed decisions keeping in view all the patient and disease associated aspects.